Analisis Survei Kepuasan Masyarakat Pada Pelayanan Kesehatan Ibu Dan Anak (KIA) Di Puskesmas Gayungan Kota Surabaya - Putri Fatahillah, Ratu Egalitarian; Noviyanti (Universitas Negeri Surabaya, 2023)
The maternal and child health service program (MCH) is carried out to ensure maternal and child health and reduce maternal and infant mortality rates which are still very high but complaints are still found related to services felt by the community. Therefore, this study aims to analyze the results of the Community Satisfaction Index (IKM) on MCH services at the Gayungan health center in Surabaya. Using a descriptive method with a quantitative approach to measure public satisfaction with MCH services provided by the Gayungan Health Center in accordance with the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for the Preparation of Community Satisfaction Surveys for Public Service Organizing Units. The sampling technique uses Accidental Sampling with a population of 1,440 people and a sample of 94 people, using data collection techniques, namely observation, questionnaires, interviews, and documentation. The results showed that the value of SMIs for MCH services was included in the category